Genome sequence of Vibrio sp. OULL4 isolated from shellfish - Vengadesh Letchumanan; Wen-Si Tan; Wai-Fong Yin; Kok-Gan Chan (Progress in Microbes and Molecular Biology)
The members of Vibrionaceae family are Gram-negative bacterium are ubiquitous in marine and estuarine environments. This diverse group of bacteria include many pathogenic strains that potentially cause infection to human and aquaculture animals. Vibrio cholerae, Vibrio parahaemolyticus and Vibrio vulnificus are among the few recognized as a major, worldwide cause gastroenteritis, particularly in countries where seafood consumption is high. The control of these vibrios has been a hurdle due to the rising numbers of antibiotic resistant strains in the environments. We report the genome sequence of Vibrio sp. OULL4 isolated from shellfish. The availability of this genome sequence will facilitate the study of its antimicrobial traits, as well as add our knowledge of Vibrio sp. diversity and evolution.